Food security status and body chemical changes among young adults / Nur Atiqah Alias - Alias, Nur Atiqah (2016)
Food insecurity, the inability to have sufficient, safe and nutritious food for an active and healthy life, was found to be closely associated with adverse health outcomes. This study was carried out to determine lipid profile (TC, TG, HDL, and LDL), inflammatory marker (hs-CRP), molecular changes on gene expression of peroxisome proliferator-activated receptor gamma (PPAR-y) and endothelial dysfunction (sE-Selectin) with food security status, especially among young adults. A cross-sectional comparative study among participants between 18 to 25 years old (n=124) who were selected through the Adults Food Security Survey Module (AFSSM) and participated in blood draw procedures. Well-established blood markers of lipid profile and inflammatory marker were measured. Percentage of food secure individuals (56.5%) was slightly higher than food insecure (43.5%). An independent-samples r-test was conducted to compare the food security status on the all parameters. Mean of hs-CRP (0.660±0.473 mg/L) was higher in food secure group, with all other variables showed higher measurements among the food insecure groups, while TC (5.087±0.647 mmol/L), HDL (1.800±0.299 mmol/L) and LDL (2.956±0.573 mmol/L)], relative normalized expression (RNE) of PPAR-y (1.188), and sE-selectin (3867.28±793.34 pg/mL) were high for food insecure respectively. However, no significant association (p>0.05) was found between all parameter except sE-selectin. In conclusion, this study showed that food insecurity experienced was influenced body chemical, physical and molecular changes. Regardless, current data provides knowledge and understanding of food insecurity experienced by young adults in a university campus and may help them in making nutritious food choices and be appreciative and aware of the risk of chronic illnesses which should have started at a young age.